"Doppelte Politikverflechtung" als Bestimmungsfaktor der Agrarstruktur- und der Agrarumweltpolitik in der BR Deutschland - Peter Mehl; Reiner Plankl (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– 999#Double interlocked federalism: The case of agri-structural and agri-environmental policies in the Federal Republic of Germany. A large portion of the agri-structural policies and agri-environmental policies in the Federal Republic of Germany are decided within the framework of complex decision-making structures and fiscal responsibility at different political levels (the federal states, the national government, and the European Union), resulting in "double-interlocked federalism". This paper describes the specific institutional configuration and its historical development, and presents a financial analysis of the development plans for rural areas in selected federal states to illustrate the increasing role of interlocked federalism. The interplay between the political levels took an unexpectedly flexible, and between the various states heterogeneous, form. All in all, however, the results did not corroborate the theoretical point of view suggesting a "joint decision trap."
Keywords: 330; Agrarstruktur; Umweltpolitik; Deutschland